ANTIBACTERIAL ACTIVITY STUDY (IN SILICO & IN VITRO) OF SOME COUMARIN MOLECULES AS LIGANDS AGAINST STREPTOCOCCUS PYOGENES BACTERIA - Latif, Abdalkader Saeed; Ali, Ihab Q.; Al-Asadi, Ammar Basim; Huno, Shahla Hussien (Eastern Ukrainian Medical Journal, 2025)
Background: Coumarin derivatives have emerged as a potential antimicrobial agent due to their broad spectrum of biological activities.Objective: Antibacterial activity against Streptococcus pyogenes is analyzed by the study of binding potentials and efficiencies of five coumarin ligands (L1, L2, L3, L4, L5) were compared to the conventional antibiotic. Clinical samples were collected from Iraqi patients attending the teaching hospital from June to October of 2023. Streptococcus pyogenes was isolated and characterized; 23 of these were confirmed by the VITEK 2 system. The susceptibility testing of the different isolated bacteria to a range of antibiotics, including Sulfamethoxazole, was carried out using the disc diffusion.Methods: The resistant ones were further tested with the coumarin molecules ligands (L1, L2, L3, L4, L5) using the agar well diffusion method.Results: Ligand number L3 showed the highest binding affinity for the Streptococcus pyogenes enzyme glycosyltransferase with a binding energy of (-38.7 Kcal/mol), representing the strong inhibiting potential of the drug. Resistance in clinical isolates was 32% to Sulfamethoxazole and showed variable susceptibility patterns to other antibiotics tested. Among these resistant strains, L3 has shown the strongest antibacterial activity, its MIC equal to (256 µg/ml), exceeding Sulfamethoxazole, while on the other hand, ligands L1, L4, and L5 gave moderate antibacterial activities, while L2, on the other hand, was found to be the least active because it gave an MIC value of (1024 µg/ml). In this study, ligand L3 was identified as a strong antibacterial agent against Streptococcus pyogenes, particularly in strains which are resistant to Sulfamethoxazole.Conclusion: L3 molecule has strong binding affinity and effectiveness to bind directly with the side chain of an amino acid, which conforms to the active side of the glycosyltransferase enzyme in target bacteria. It blocked it and led to malfunctioning of the target enzyme. Therefore, it is a promising alternative to the traditional antibiotics. Further research on coumarin derivatives may help in getting new antibiotic-resistant illness treatments.